Regional Wage Differentiation and Qualitative Determinants of Economic Development: Evidence from Poland - Kapela, Magdalena; Kwiatkowski, Eugeniusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The article shows the differences in salaries in Polish voivodeships and between poviats of individual voivodeships. It also identifies factors, particularly qualitative development ones, which affect them. Research Design & Methods: Ranking, spread indices, coefficients of variation, and grouping methods were used. Parameters of panel econometric models with random effects and fixed effects were also estimated. Findings: In the years 2010–2020, wage variation between voivodeships decreased slightly. This indicates a weak process of sigma convergence, but the data about average annual wage growth do not show a clear tendency to beta convergence. The highest average wages were found in Mazowieckie, Śląskie and Dolnośląskie voivodeships, and the lowest in Warmińsko-mazurskie, Podkarpackie, Lubuskie, Kujawsko-pomorskie and Świętokrzyskie. The econometric analysis confirmed that the following factors had a positive impact on wage levels: labour productivity, the share of people with higher education, the number of patents and the share of innovative enterprises, and a negative impact of the unemployment rate. The 2020 pandemic also had a significant positive impact on wages in voivodeships. Implications / Recommendations: The analyses confirm a significant impact of qualitative development factors on wages in voivodeships. Contribution: The research complements the Polish literature on the impact of qualitative development factors on regional differences in wages and confirms the validity of using panel models for this type of analysis.